Ponto de vista narrativo de mães que perderam seus filhos de maneira violenta: relatos de rupturas biográficas - Aires, Maria Neurielli Figueiredo Cardoso (2023)
This thesis will aim to analyze the narrative point of view of bereaved mothers who lost their children to violent death, considering the issue of rupture (MAIA-VASCONCELOS; 2022). We used as corpus autobiographical narratives of mothers who lost their children in a traumatic way. This corpus was provided by Silva (2015), and for that we asked authorization from two mothers through an TCLE (free and informed term of commitment) so that we could proceed with our analyses. For that, we established, as specific objectives: a) to analyze the narrative positioning of the subject when telling his story considering the notion of Point of View (PDV) of Rabatel; b) describe the distinction between mourning for violent and non-violent death taking into account the circumstances of the event and the iteration of occurrences in the narrative; c) analyze the functioning of autobiographical narratives observing the notion of rupture according to Maia-Vasconcelos (2022) and Bury (1982). The theoretical foundation on which we based these objectives comes from the theoretical context that we elaborated from reflections on discourse in the light of Bakhtin's (2003) theoretical perspectives and interdiscourse under the bias of Maingueneau (2008), Bourdieu (2003) and Maia-Vasconcelos (2022) ; the concept of narrative in light of the theories of Pineau (1996), Maia-Vasconcelos (2005; 2018; 2022), Jerome Bruner (2014); the notion of PDV from the perspective of Rabatel (2016) and Genette (1989) and aspectuality in the light of reflections by Castilho (1968), Godoi (1992), Lima (2009) and Travagia (2016). The results showed a triad that structurally represents a narrative analyzed within the context of HIVI studies. This triad, as we demonstrate in the thesis, is composed: by the mother's narrative, by the violence against the child and by the rupture marked by the loss of the child. In the mother's narrative we find what we call in this thesis a narrative-lived PDV, because from this PDV we can analyze the position of this subject who narrates his story. At the other end of this triangulation, violence is marked by circumstantiality, which triggered these narratives and how iteration proves to be a fundamental part of this type of narrative. Finally, the construction of the PDV and the notion of iteration that these narratives present is only possible due to what we call biographical ruptures in the thesis, a key moment in the life of the subject that will constitute the structure in which the event will be narrated. These results allow us to conclude that the analyzes of autobiographical narratives marked by a rupture need to take into account aspects of the narrative point of view, as well as notions of verbal aspectuality, in addition to being able to contribute to a more plural approach to the narrative study in the field of Linguistics.